A Sense of Place and the Rural Adult Learner - Cindy Kittredge (Adult Education Research Conference, 1999)
Confirming the importance of keeping the individual squarely at the center of the learning experience, this qualitative study of Montana ranchers describes how a sense of place, in this case an expansive rural landscape, provides Responsive Learners with a unique way of seeing, of communicating, of knowing, and of doing.